Implikasi Hukum Perluasan Perkebunan Sawit Skala Besar Terhadap Perlindungan Lahan Pertanian Pangan Berkelanjutan - Jaenal Mutaqin; Muhamad Muhdar; Haris Retno Susmiati (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to analyze the legal implications arising from the disharmony between regulations governing the expansion of large-scale oil palm plantations and the protection of Sustainable Food Agricultural Land (LP2B), as well as to examine the implementation of food agricultural land protection policies in Kutai Kartanegara Regency. The research employs an empirical legal method with a socio-legal approach, combining statutory analysis, document review, and interviews with relevant stakeholders. The data were analyzed qualitatively using the theories of legal politics and legal disharmony. The findings reveal the existence of regulatory disharmony in vertical, horizontal, and implementation dimensions. Regulations that support the expansion of oil palm plantations through licensing simplification, the extension of Land Use Rights (Hak Guna Usaha/HGU), and investment-oriented policies following the enactment of the Job Creation Law tend to conflict with the objectives of sustainable food agricultural land protection. The study also finds that the conversion of food agricultural land into oil palm plantations in Kutai Kartanegara is predominantly carried out independently by farmers as a result of economic pressures and socio-economic structural changes influenced by the presence of large-scale plantation companies. Furthermore, spatial planning decision-making processes demonstrate the dominance of investment interests over food land protection. Therefore, regulatory harmonization, the strengthening of LP2B protection instruments, and the provision of economic incentives for farmers are necessary to maintain the sustainability of food agricultural land and support national food security.